Sustainable Development Goal 3 Health and Well-being of Ageing in Hong Kong - Fong, Ben Y. F. (Routledge Focus on Public Governance in Asia, 2022)
Sustainable Development Goals (SDGs) aim to develop a better and sustainable future for the world and the goals are part of an action plan to address poverty, hunger, health, gender equity and various pressing world issues. One of these goals looks at health and wellness. Ageing populations have become a crucial issue worldwide and this short monograph explores ageing and how the consequences of an ageing population may affect our health care system through the case study on Hong Kong's population. The book looks at several critical health issues related to ageing. The elderly, particularly those with low socioeconomic status, rely more on the acute-centric care rather than primary care. The book suggests that secondary care service may only be effective to limited extent as a healthcare measure and an optimum health care system should be one that focuses on primary care. The authors put forth a compelling argument for disease prevention and screening schemes and explain how they are more cost-effective and beneficial to the society and the system. This thoughtful book will provide beneficial insights into the relationship of ageing and sustainable development goals in the context of health and wellness for policy makers and healthcare professionals.